Mengungkap Makna Tersirat di Balik Lagu "Tarot": Analisis Psikolinguistik Terhadap Diksi dan Metafora - Dessy Saputry; Rohmah Tussolekha; Uswatun Hasanah; Chintia Apriyani; Putri Maisya Silvia; Wulan Agustin; Muhammad Rohman (Journal of Innovative and Creativity, 2025)
This research aims to uncover the implicit meanings in the lyrics of “Tarot” by .Feast through a psycholinguistic analysis of the diction and metaphors used. The study employs a qualitative descriptive approach using content analysis, focusing on linguistic representations that reflect the songwriter’s psychological state. The data, consisting of the song’s lyrics, were analyzed by identifying linguistic units containing connotative and symbolic values. The findings reveal that the use of connotative diction such as “mirror,” “destiny,” and “shadow” reflects introspective processes and inner conflicts, while metaphors like “sailing among shadows” symbolize the existential journey of humans in their search for life’s meaning. The psycholinguistic analysis shows that language in the lyrics functions not only as an aesthetic means of communication but also as a cognitive and emotional medium that portrays the dynamics of human thought and feeling. Thus, the musical work “Tarot” serves as a profound reflection on the relationship between language, thought, and emotion within the context of modern art.